Social learning in MMOG: an activity theoretical perspective - Ang, Chee Siang; Zaphiris, Panayiotis (My University, 2008)
Purpose – Recently, researchers have begun investigating the learning process that occurs within computer games (learning to play), as opposed to studying games that support explicit learning for educational purposes (playing to learn). With the increasing popularity of massively multiplayer online games (MMOGs), some research has begun to look beyond individual play and is now focusing on social play. By conducting a 30 day virtual participant observation in an MMOG, namely World of Warcraft (WoW) this paper aims to identify and provide a theoretical explanation of the process of learning that takes place in such an open-ended virtual world. Design/methodology/approach – Through the lens of activity theory, the paper focuses its analysis on the tool, the goal, the activity of game playing and contradictions. Findings – It was found that social learning could occur through intrinsic and extrinsic play. Intrinsic play is play oriented toward goal completion while extrinsic play is directed toward reflection and expansion of intrinsic play. WoW is designed with tools that facilitate these types of play, and therefore learning that emerges from them. Furthermore, learning involves not only the process of acquiring knowledge and skills to accomplish certain goals, but also the process of defining the goal, thus shaping the learning process. Originality/value – The results could be used to inform game design either for social play or for social learning.
Keywords: Computer-based learning; Learning; Learning process; Video games